Teleprehabilitation during COVID-19 pandemic: the essentials of “what” and “how” - Lambert, Genevieve (Support Care Cancer, 2020)
In view of the COVID-19 pandemic and recent global events, the healthcare system and its services have been negatively affected, contributing towards extensive surgical backlogs. Oncological surgical candidates have been the most impacted by these changes and recommended self-isolation practices, which could result in emotional distress, sedentary behavior, and poor lifestyle habits. Preoperative supportive intervention, prehabilitation, has been proven to improve patients’ functional status and clinical trajectories. Presently, there is a critical need for prehabilitation to optimize patient health, as they experience extended wait times. However, in-hospital delivery may not be an ideal approach due to public health and safety measures. Telehealth is a field of research and practice, which has grown and evolved significantly in the last two decades, allowing for the remote delivery of health services. Therefore, the current commentary addresses the different modalities of telehealth delivery in perspective of their known feasibility and potential application in prehabilitation.